Antibacterial Activities of Phenolic Compounds in Miang Extract: Growth Inhibition and Change in Protein Expression of Extensively Drug-Resistant Klebsiella pneumoniae - Pannita Anek; Sutita Kumpangcum; Sittiruk Roytrakul; Chartchai Khanongnuch; Chalermpong Saenjum; Kulwadee Phannachet (MDPI AG, 2024)
The rising incidence of extensively drug-resistant (XDR) Klebsiella pneumoniae, including carbapenem- and colistin-resistant strains, leads to the limitation of available effective antibiotics. Miang, known as chewing tea, is produced from Camellia sinensis var. assamica or Assam tea leaves fermentation. Previous studies revealed that the extract of Miang contains various phenolic and flavonoid compounds with numerous biological activities including antibacterial activity. However, the antibacterial activity of Miang against XDR bacteria especially colistin-resistant strains had not been investigated. In this study, the compositions of phenolic and flavonoid compounds in fresh, steamed, and fermented Assam tea leaves were examined by HPLC, and their antibacterial activities were evaluated by the determination of the MIC and MBC. Pyrogallol was detected only in the extract from Miang and showed the highest activities with an MIC of 0.25 mg/mL and an MBC of 0.25-0.5 mg/mL against methicillin-susceptible Staphylococcus aureus, methicillin-resistant S. aureus, Escherichia coli ATCC 25922, colistin-resistant E. coli, and colistin-resistant K. pneumoniae. The effects on morphology and proteomic changes in K. pneumoniae NH54 treated with Miang extract were characterized by SEM and label-free quantitative shotgun proteomics analysis. The results revealed that Miang extract caused the decrease in bacterial cell wall integrity and cell lysis. The up- and downregulated expression with approximately a 2 to >5-fold change in proteins involved in peptidoglycan synthesis and outer membrane, carbohydrate, and amino acid metabolism were identified. These findings suggested that Miang containing pyrogallol and other secondary metabolites from fermentation has potential as an alternative candidate with an antibacterial agent or natural active pharmaceutical ingredient against XDR bacteria including colistin-resistant bacteria.